Long-Term Effects of Comprehensive Inpatient Rehabilitation on Function and Disease Activity in Patients with Chronic Rheumatoid Arthritis and Ankylosing Spondylitis - Figen AYHAN; Muharrem GEÇENE; Rukiye GÜNDÜZ; Pınar BORMAN; Rezan YORGANCIOĞLU (Archives of Rheumatology, 2011)
Objectives: We compared the inpatient rehabilitation model (IRM), provided by the physiatrist, physical therapist, rehabilitation nurse and clinical psychologist, with the home exercise model (HEM), provided by the physiatrist for the rehabilitation of patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Patients and methods: One hundred and twenty eligible adult patients [60 RA (mean age 51.8±11.7) and 60 AS (mean age 39.7±10.4)] requiring rehabilitation treatment who had not received physical therapy (PT) in the past two years were included in this study. Participants were randomly allocated into two groups IRM or HEM. The primary outcome was one of the following measures from baseline to 15 months: Disease Activity Score of 28 joints (DAS28) and Health Assessment Questionnaire (HAQ) scores for patients with RA and scores of Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) for patients with AS. Outcome assessors were blinded. General estimated marginal means of multivariate comparisons were performed for both “within-subjects” and “between-subjects” for statistical analyses. Results: Mean disease duration of patients with chronic RA and AS were 8.5±6.4 (median 7) and 8.7±7.8 (median 6) years, respectively. Changes of DAS28 and HAQ scores were better in the IRM group than the HEM group. While most of the patients with RA used combined disease-modifying antirheumatic drugs, none of the patients used anti-tumor necrosis factor agents for disease control. BASFI and BASDAI score improvements were not different in both groups. Inpatient rheumatologic rehabilitation programs improved physical function and disease activity in patients with RA and AS. However, statistically significant changes were detected in the DAS28 and HAQ scores of RA patients. Conclusion: Since patients’ functioning is a central aspect of the rheumatic diseases, and remission is rare for these diagnoses, rheumatologic rehabilitation programs should be applied to all of these patients. Inpatient care was useful for patients with RA in contrast to patients with AS. It might be related to more resting periods in inpatient care as opposed to the usual care or ineffective drug therapy for continuing disease process in patients with AS.